Endovascular therapeutic options for the treatment of aortoiliac aneurysms - MASSIÈRE,BERNARDO (2016)
ABSTRACT About 20% of patients with abdominal aortic aneurysms have associated iliac aneurysms. Distal sealing during the endovascular treatment of aortic-iliac aneurysms is a challenge that has led to the emergence of several technical options to achieve this goal over the years. Internal iliac artery embolization is associated with the risk of ischemic complications, such as gluteal necrosis, lower limb neurological deficit, colonic ischemia, impotence and gluteal claudication. This article summarizes the technical options for endovascular treatment of aortoiliac aneurysms with different approaches to preserving the patency of internal iliac arteries.